2017
DOI: 10.4049/jimmunol.1700586
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Functional Characterization of Circulatory, Splenic, and Hepatic NK Cells in Simian Immunodeficiency Virus–Controlling Macaques

Abstract: NK cells are key components of the immune system due to their rapid response potential and their ability to mediate cytotoxic and immunomodulatory functions. Additionally, NK cells have recently been shown to persist for long periods in vivo and to have the capacity to establish immunologic memory. In the present study we studied the phenotype and function of circulatory and tissue-resident NK cells in a unique cohort of SIV controlling rhesus macaques that maintained low to undetectable levels of viremia in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 42 publications
0
13
1
Order By: Relevance
“…28,31 Nevertheless, close phenotypic analogies have been found between macaque and human NK cell subpopulations, and functional studies have revealed similar behavior in both species. [32][33][34][35] We previously uncovered the phenotypic complexity and diversity of innate myeloid cells in the blood and the impact of vaccinations on the dynamics of their subset composition by mass cytometry 27 in cynomolgus macaques immunized with a recombinant MVA HIV-B.…”
Section: Nk Cells Are Innate Lymphoid Cells That Can Constitutively Kmentioning
confidence: 99%
See 1 more Smart Citation
“…28,31 Nevertheless, close phenotypic analogies have been found between macaque and human NK cell subpopulations, and functional studies have revealed similar behavior in both species. [32][33][34][35] We previously uncovered the phenotypic complexity and diversity of innate myeloid cells in the blood and the impact of vaccinations on the dynamics of their subset composition by mass cytometry 27 in cynomolgus macaques immunized with a recombinant MVA HIV-B.…”
Section: Nk Cells Are Innate Lymphoid Cells That Can Constitutively Kmentioning
confidence: 99%
“…In addition, both human and macaque NK cells express NKp46, but in macaques, NKp46 may not be expressed by all NK cell subpopulations . Nevertheless, close phenotypic analogies have been found between macaque and human NK cell subpopulations, and functional studies have revealed similar behavior in both species …”
Section: Introductionmentioning
confidence: 99%
“…Spleen and inguinal lymph node (LN) biopsies were dissected and passed through a 40 µm cell strainer after lysis of red blood cells (RBCs). The cells were washed and resuspended in R10 media (RPMI 1640 containing 10% FBS, 2 mM L-glutamine, 1% nonessential amino acids, 1% sodium pyruvate, and antibiotics) (30)(31)(32). Bone marrow cells were isolated by density gradient centrifugation on Ficoll.…”
Section: Sample Collection and Preparationmentioning
confidence: 99%
“…The biopsy specimens were digested with collagenase (2 mg/ml; Sigma-Aldrich), and single cells were harvested as described (41). PBMCs were processed by density gradient centrifugation over Ficoll as described (27). PBMCs were frozen in FBS containing 10% DMSO and stored in liquid nitrogen until use.…”
Section: Sample Collectionmentioning
confidence: 99%
“…In the presence of HIV/SIV-specific Abs, NK cells exert potent antiviral responses to control infection (24)(25)(26). Similarly, in the SIV rhesus macaque model, NK cell-mediated ADCC activity was inversely correlated with viral loads (VLs) in chronically infected macaques (27). Polyfunctional humoral immune responses increase the antiviral capacity of innate immune cells, including NK cells of elite controllers (24).…”
mentioning
confidence: 99%